Brief-Guided Internet-Based Cognitive Behavioural Therapy for People with Emotional Distress During the COVID-19 Pandemic. - Young, Daniel Kim-wan; Carlbring, Per; Ng, Siu-man; Daphne, Cheng Yi Ting; Ng, Petrus Yat-nam; Qi-rong, Joseph Chen; Tam, Cherry Hau Lin; Yeung, Jerf Wai Keung (Clinical Social Work Journal, 2026)
This pilot study aimed to investigate the acceptability and effectiveness of a brief-guided internet-based cognitive behavioural therapy (iCBT) for people with emotional distress during the COVID-19 pandemic. Using a quasi-experimental research design with a 3-arm study, eligible participants were assigned to a group with student counsellors (n = 24), a group with counsellors (n = 23) or a non-active control group (n = 21). Participants received eight online modules and regular support via telephone counselling or video conferencing app (Zoom) from a counsellor or student counsellor during a 5-week intervention period, while the control group did not receive any intervention during the intervention period. An adherence rate of 85.10% was observed. The results of the 3 (group) × time (pre vs. post) repeated-measures analysis of covariance showed that the student counsellor and counsellor groups demonstrated significantly greater reductions in total emotional distress (partial η = 0.10) and stress (partial η = 0.14) than the control group. In addition, student counsellors and counsellors produced comparable intervention effects, and telephone counselling and Zoom support produced comparable intervention effects. This pilot study supports the acceptability and effectiveness of brief-guided iCBT for people with emotional distress during the COVID-19 pandemic.